Menjembatani Teks dan Realitas: Analisis Interpretasi Kuntowijoyo terhadap Konsep The Chosen People dalam QS Ali Imran/3:110 - Rasyid, Muhammad Dirman; Muh. Ilham Usman; Anugrah Reskiani (STAIN Majene, 2024)
The concept of “The Chosen People” in Islam, as reflected in Surah Ali Imran 3:110, has long been a subject of theological discourse. However, contemporary interpretations of this concept, especially in the context of plural societies, remain underexplored. This research examines Kuntowijoyo's progressive exegesis of Surah Ali Imran 3:110, focusing on the reconceptualization of “The Chosen People” within the framework of modern Indonesia. Employing a qualitative methodology with a critical hermeneutic approach, this study analyzes Kuntowijoyo’s works and situates them within a quasi-objectivist progressive exegesis framework. The main findings reveal that Kuntowijoyo transforms the concept “The Chosen People” from an exclusive understanding into a universal ethical mandate, operationalized through three pillars: humanization (amar ma’ruf), liberation (nahi munkar), and transcendence (tu’minuna billah). Further analysis suggests that this interpretation offers a new paradigm for understanding the role of Muslims in plural societies, with significant implications for socio-religious activism and interfaith dialogue. This study contributes to the literature on contemporary Quranic hermeneutics and the sociology of religion, while highlighting the potential of progressive exegesis to bridge the gap between classical religious doctrine and modern social realities. The research also opens avenues for further exploration of the actualization of Quranic values in the context of a global multicultural society.